PEMBEKALAN APLIKASI SPSS TERHADAP SISWA SMA MUHAMMADIYAH 3 JEMBER - Gunasti, Amri; Putra, Unas Aleansa Abenk; Ariadana, Mohammad Luthfie; Hamdani, Naufal Zakin; Key Maulana; Ramadhan, Gilang Akbar; Roy Bachtiar; Asri, Andi Batara Rangga; Kumala, Cynthia Intan; Kusuma, Kia Candra; et al. (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
One of the software technologies for processing highly accurate and well-tested statistical data used to process data is the SPSS application. However, so far this application is not very familiar to high school students even though they really need it in data processing activities in the learning process. Therefore, students of the Civil Engineering Study Program at Muhammadiyah Jember University took the initiative to transfer technology to Muhammadiyah 3 Jember High School students in the form of community service. The purpose of this service activity is first so that students of Muhammadiyah 3 Jember High School (SMA) have the expertise to run SPSS to process data. The second objective of this activity is to inform Muhammadiyah 3 Jember High School students about the importance of data processing to support making the right decisions in everyday life. The methods used in this activity are determination of service targets, coordination, field surveys, implementation of training, implementation of discussion activities and evaluation of the success of the service program. The results of analyzing the pre-test and post-test scores show that the ability of Muhammadiyah 3 Jember High School (SMA) has increased very significantly. the average pre-test score of the 5 groups is 50.76 with a standard deviation of 7.054. While the average value of the post test was 76.113 with a standard deviation of 7.054. While the average post test value is 76.113 with a standard deviation value of 10.113. — Salah satu teknologi perangkat lunak untuk mengolah data statistik yang sangat akurat dan telah teruji dengan baik yang digunakan untuk mengolah data salah satunya adalah aplikasi SPSS. Hanya saja selama ini aplikasi ini tidak terlalu familiar bagi Siswa Sekolah Menengah Atas walaupun mereka sangat membutuhkannya dalam aktivitas mengolah data dalam proses belajar. Oleh karena itu, Mahasiswa Program Studi Teknik Sipil Universitas Muhammadiyah Jember berinisiatif untuk melakukan transfer teknologi kepada siswa SMA Muhammadiyah 3 Jember dalam bentuk pengabdian. Tujuan kegiatan pengabdian ini adalah pertama agar siswa Sekolah Menengah Atas (SMA) Muhammadiyah 3 Jember memiliki keahlian untuk menjalankan SPSS untuk mengolah data. Tujuan kedua dari kegiatan ini adalah untuk memberi informasi kepada siswa Sekolah Menengah Atas (SMA) Muhammadiyah 3 Jember mengenai pentingnya pengolahan data untuk menunjang pembuatan Keputusan yang tepat dalam kehidupan sehari-hari. Metode yang digunakan dalam kegiatan ini adalah penentuan target pengabdian, koordinasi, survei lapangan, pelaksanaan pelatihan, pelaksanaan kegiatan diskusi serta evaluasi keberhasilan program pengabdian. Hasil analisa nilai pre test dan post test menunjukkan bahwa kemampuan sekolah Menengah Atas (SMA) Muhammadiyah 3 Jember telah meningkat sangat signifikan. nilai rata – rata pre test dari 5 kelompok adalah 50,76 dengan nilai standar deviasi sebesar 7,054. Sedangkan nilai rata – rata post test 76,113 dengan nilai standar deviasi sebesar 10,113.